Los presupuestos teóricos y prácticos del miedo como causa de inexigibilidad de la responsabilidad penal - Suñez Tejera, Yoruanys (2023)
The insuperable exculpation of fear has been object of dissimilar controversies. The law is some cases is contradictory and what is expressed, transcends to the Cuban judicial practice where there is an indetermination to the moment of appreciate it and it also gets confused with other exculpatory circumstances. The research aims to formulate the theoretical and practical budgets to be carried out to recognize the insuperable exculpation of fear. It is necessary to determine it according to the concurrent c ircumstances, then it corresponds to demand to the subject to act in a different way to how it was done. As a result theoretical and practical budgets are gotten, to recognized the insuperable exculpation of fear as an inexigibility cause of penal responsi bility. It contributes to a correct regulation of the insuperable exculpation of fear with a level of inexigibility in which no corresponds to demand to the subject to act in a different way of how it was done.